Altered microbiome in chronic kidney disease: systemic effects of gut-derived uremic toxins - Lau, Wei Ling; Savoj, Javad; Nakata, Michael B; Vaziri, Nosratola D (Clinical science (1979), 2018)
In chronic kidney disease (CKD), influx of urea and other retained toxins exerts a change in the gut microbiome. There is decreased number of beneficial bacteria that produce short-chain fatty acids, an essential nutrient for the colonic epithelium, concurrent with an increase in bacteria that produce uremic toxins such as indoxyl sulphate, -cresyl sulphate, and trimethylamine-N-oxide (TMAO). Due to intestinal wall inflammation and degradation of intercellular tight junctions, gut-derived uremic toxins translocate into the bloodstream and exert systemic effects. In this review, we discuss the evidence supporting a role for gut-derived uremic toxins in promoting multiorgan dysfunction via inflammatory, oxidative stress, and apoptosis pathways. End-organ effects include vascular calcification, kidney fibrosis, anemia, impaired immune system, adipocyte dysfunction with insulin resistance, and low turnover bone disease. Higher blood levels of gut-derived uremic toxins are associated with increased cardiovascular events and mortality in the CKD population. Clinical trials that have examined interventions to trap toxic products or reverse gut microbial dysbiosis via oral activated charcoal AST-120, prebiotics and probiotics have not shown impact on cardiovascular or survival outcomes but were limited by sample size and short trials. In summary, the gut microbiome is a major contributor to adverse cardiovascular outcomes and progression of CKD.